Supply Chain Analysis of Fresh Fruit and Vegetables in Germany - Volker Hart; Aikaterini Kavallari; Peter Michael Schmitz; Tobias C. Wronka (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2007)
With a population of 82.5 million, the German market is the largest in the EU and therefore of special interest for the trade partners. Despite an unsatisfying economic development in the last years (lowest GDP growth in the EU and rising unemployment, see Table 9 in the annex) Germany is still a very attractive market with well funded consumers. Although agriculture has a small and declining contribution to the country's gross domestic product, in the wider definition of the agribusiness, it is still one of the most important sectors with regard to turnover and employment. Taking consumers' expenditure for food as a proxy for the total turnover of the agribusiness yields a figure of 240 billion - in 2003, nearly as much as the turnover of the car industry in Germany. In total, 4.5 million people are employed in the agribusiness, which is 11.6% of Germany's total labour force. Among agricultural markets, the market of fruit and vegetables is of special interest for the trade with Mediterranean countries and also of special importance for the food industry and the food consumption. In 2003 consumers' expenditure for fresh fruit and vegetables were more than 10 billion exteuro. The processing industry of fruit and vegetables generated another 6.5 billion - turnover, demonstrating the importance of fruit and vegetables in Germany. Bearing in mind that the self sufficiency ratios for fruit and vegetables in Germany are low (13% respectively 50%), the extent of market opportunities for the Mediterranean countries become obvious. Against this background it is the objective of this report to analyse the supply chain of fresh fruit and vegetables in Germany. In the second chapter the current market situation is briefly presented with regard to production, consumption and trade in Germany. Other aspects covered in this chapter are the demographic structure in Germany, important consumer trends and food quality issues. The third chapter is devoted in depth to the analysis of the supply chains for both fruit and vegetables. In this chapter the different actors and market channels are described with regard to their task and importance in the supply chain. In the fourth chapter the overall institutional structure is analysed. After the conclusions in the fifth chapter extensive tables and figures can be found in the annex.
Keywords: 330